2007
DOI: 10.1007/bf02912882
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study of Carcino Embryonic Antigen & Cancer Antigen 15.3 in pretreated female breast cancer patients

Abstract: Carcino Embryonic Antigen (CEA) and Cancer Antigen15.3 (CA15.3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…However, regression analysis showed low prediction. Our findings is the same as the study by Thriveni et al, 2007 that displayed regression analysis for predicting serum levels of CEA and it was also low in relation to stage, tumor size, node and tumor grade. They also displayed that serum CA15-3 levels were associated with advanced stages and larger tumor sizes (>5cm).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, regression analysis showed low prediction. Our findings is the same as the study by Thriveni et al, 2007 that displayed regression analysis for predicting serum levels of CEA and it was also low in relation to stage, tumor size, node and tumor grade. They also displayed that serum CA15-3 levels were associated with advanced stages and larger tumor sizes (>5cm).…”
Section: Discussionsupporting
confidence: 89%
“…This marker plays the biological roles such as cell adhesion, immunity and it is responsible for metastasis (Thriveni et al, 2007). However, MUC1 is overexpressed and improperly glycosylated in malignant epithelial cells especially tumor cells (Barros et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Uehara et al [ 6 ] and Atoum et al [ 11 ] found significant differences in CA15-3 expression levels in different stages of breast cancer. In addition, Thriveni et al found that serum CEA levels did not have any significant correlation in breast cancer patients prior to treatment [ 17 ]. Samy et al showed that preoperative serum levels of CEA of breast cancer patients were significantly higher compared with the levels of the control group [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…But there are few reports concerning label-free detection of carcinoembryonic antigen (CEA) with an aptamer modified FBAR biosensor. CEA is one of the most widely used tumor markers in the clinical diagnosis of breast, colorectal, and lung cancer making monitoring of CEA very important for clinical tumor diagnoses [8][9][10].…”
Section: Introductionmentioning
confidence: 99%